Morar e (sobre)viver na metrópole goianiense : análise da mobilidade da segregação residencial na região noroeste de Goiânia - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The present research deals with the mobility present in the process of residential segregation. This mobility is identified in the displacement and organization of social classes in urban space, from the differentiated materialization of income. In Goiânia, this movement was present in the Northwest Region of Goiânia. It was the result of a combination of two well-defined centralities - one materialized by the representatives of the Brazilian Democratic Movement Party (PMDB) and the other party formed by the Brazilian Social Democracy Party (PSDB). These two centralities were effective, from the allocation of services, public and private facilities in two axes of road: in Avenida do Povo and later in Avenida Mangalô. In the Avenue of the people the services implanted were - old people's house; schools; Police stations, medical assistance units. At Avenida Mangalô - bus terminal; Bank branches and Citizen Assistance Unit. In this movement of centralization of public services, other agents became present: landowners; Real estate developers and owners of the means of production, inserting new forms and contents in the segregated space. One of the forms inserted by these agents, we highlight the refunctionalization of the urban space of Avenida Mangalô - resulting in the replacement of residences by commercial rooms on the road. In this course of centralization of public and private services, the neighborhoods surrounding Mangalô were involved in the valorization process. This valorization provoked by the dimension of the centrality produced in the route simultaneously attracted and expelled populations to / from the neighborhoods Morada do Sol and Recanto do Bosque. Based on this premise, the research was developed seeking to understand the role of agents producing urban space for the mobility of residential segregation in the Northwest Region of Goiânia. Emphasis was given to the neighborhoods surrounding Avenida Mangalô, due to the size of the public services materialized in the avenue, as well as the alterations provoked in the neighborhoods. In relation to the methodological procedures, we sought to represent cartographically the income distribution of heads of families; As well as the households in the neighborhoods surrounding Mangalô. These data refer to the demographic census of the Brazilian Institute of Geography and Statistics (IBGE) in the year 2000 and 2010 and allowed to demonstrate where some income ranges were concentrated in the neighborhoods: Morada do Sol and Recanto do floresta Implementation of public and / or private services and facilities at Avenida Mangalô. In addition, bibliographical research was carried out; Field and mapping of information regarding income, residential displacements and the dynamics of the interviewees that are spatialized in the studied districts.
Keywords: Segregação Residencial; Refuncionalização; Mobilidade da Segregação Residencial; Goiânia/GO/Brasil; Região Noroeste de Goiânia; Residential Segregation; Refunctionalization; Mobility of Residential - Segregation; Goiânia/GO/Brazil; Região Noroeste de Goiânia.; GEOGRAFIA REGIONAL::REGIONALIZACAO; GEOGRAFIA HUMANA::GEOGRAFIA URBANA